Adolescents’ activity handbook for family intervention for the mitigation of online drug trafficking: module development and feasibility of implementation - Alwi, Azlin; Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Mohamed Iqbal, Mimi Iznita (2019)
The Adolescents’ Activity Handbook is designed to provide knowledge and skills to adolescents about drugs, resilience, adolescent’s development, social media, and laws regarding drug use and abuse. This Handbook contains various important topics which include knowing self and others, managing stress, differentiating between positive and negative thinking, situational awareness, and the dangers and risks of social media. This Handbook contains five modules: (i) knowledge; (ii) resilience; (iii) family; (iv) Internet and social media; and (v) laws.